Need Assessments of Learning Model for Anemia Prevention Among Vocational High School Students - Ahla Hulaila; Zahroh Shaluhiyah; Sri Winarni (Universitas Airlangga, 2024)
Background: The sustainable development goals (SDGs) provide an integrated framework of targets and indicators, including the elimination of stunting. The nutritional status of adolescent girls is a strong determinant of the health, low birth weight, and stunting of their future offspring. The health problems for adolescents or students include anemia. If the incidence of anemia in students is not addressed immediately, it will have an impact in the future, namely on students experiencing anemia when they're pregnant in future. So, It is necessary to develop a learning model for anemia prevention for students. Aims: This research aims to analyze the students needed for the anemia prevention learning model. Method: This article used a qualitative descriptive method with a case study approach. The informants are 7 students, 1 health center teacher, and 1 vice principal. Data collection was conducted by in-depth interviews and FGD. Data were analyzed using content analysis methods. Result: The practice of taking iron supplements for Students is low, Eating patterns are only 2 times a day and they have difficulty eating, the informants didn`t have the habit of physical activity at home and have unhealthy sleeping habits. Students need educational content about anemia and healthy eating patterns. Students like the P5 (Pancasila Student Profile Strengthening Project) Method. And the communicator is a teacher or other person who understands about anemia. Conclusion: Student behavior related to anemia prevention is not good. It is necessary to educate students about the prevention of anemia. The development of the learning model taken is the P5 Module with the theme of Anemia Prevention.